IMPLEMENTASI SUPERVISI KLINIS DALAM MENINGKATKAN PROFESIONALISME GURU - ASTUTI, ASTUTI (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
This journal discusses the implementation of clinical supervision in improving teacher professionalism. Clinical Supervision is a guidance process aimed at assisting professional development of teachers / prospective teachers, especially in teaching performance based on observation and analysis of data accurately and objectively as guidance for the change of teaching behavior. This supervision puts pressure on the process of